Personological Creation of Language: The Feminist Perspective - Olatunbosun, Taofeek; Oduwole, Olamide (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This research stems from Helene Cixous’s call for women to invent their language – the language of feminism – by interpreting their identities as a science of feminine creation. This science is a protest of women’s subjugation and exploitation using symbolic language to question male supremacy. Thus, this research investigates sexual differentiation as related to language differentiation between men and women. This investigation aims to develop standards and deploy a feminist-specific language known as l’ecriture feminine. Significantly, the argument seeks to challenge masculine realities, judgments and perspectives manifested in language deployment. A creative writing-based methodology is used, and the primary author is Akachi Adimora-Ezeigbo, together with other relevant authors and feminist critics who have demonstrated in their works, women’s patterns of reasoning and language. The goal is to create a language of feminism that is a conscious effort to erase or contrast the language of patriarchal imaginary order, which is fundamental in language codification. Consequently, female and male writers who share this position are encouraged to develop and rewrite popular narratives to establish the language of feminism as a field of exploration and use in the modern world.